Risk of falls and its association with activities of daily living and depression among elderly residing in a rural area in Bangalore, Karnataka - Kannan, Radhika; Fathima, Farah Naaz; Agrawal, Twinkle; Mohan, Joseph; Retnakaran, Rithesh; Mudhol, Snehal Ramesh (International Journal of Research in Medical Sciences, 2022)
Background: According to 2011 censes, elderly account for 8.6% of Indian population and is projected to become 20% by 2050. Early identification and prevention of fall-related factors would play a vital role in reducing the health costs in elderly. The objective of the study was to assess the risk of falls among elderly residing in Mugalur subcentre, Bangalore Urban. Methods: A cross-sectional study was conducted at the ten villages of Mugalur subcenter, from March-May 2019 using a structured questionnaire that was administered through a face-validated interview. Systemic random sampling was done from the ten villages, proportionate allocation was done to reach a calculated sample size of 220. Timed up and go test (TUG) was done for all participants. Results: Mean age of the study population was 69.05±8.3years. Among the study subjects, 40 (18.2%) had moderate risk of fall and 9 (4.1%) were seen to have high risk of fall. 26 (11.8%) subjects had a fall in past one year. TUG test showed a median value of 18.5 seconds, and 179 (18.4%) elderly had TUG result ≥13 sec. According to Geriatric Depression scale (GDS-15), 18 (8.2%) subjects were found to be severely depressed. Significant association was seen between the GDS-15 scores and risk of falls according to Fisher’s exact test. The mean TUG score was shown to have a significant association with the risk of falls according to ANOVA. Conclusions: Moderate to high risk of fall is seen among 22.3% of the elderly. Significant association was seen between age, TUG score and depression with risk of falls.